2013
DOI: 10.1039/c3cp44289f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind sulfur promoted oxidation of methane

Abstract: The promoting effect of SO2 on the activity for methane oxidation over platinum supported on silica, alumina and ceria has been studied using a flow-reactor, in situ infrared spectroscopy and in situ high-energy X-ray diffraction experiments under transient reaction conditions. The catalytic activity is clearly dependent on the support material and its interaction with the noble metal both in the absence and presence of sulfur. On platinum, the competitive reactant adsorption favors oxygen dissociation such th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 79 publications
(233 reference statements)
2
36
0
Order By: Relevance
“…These bands increased in intensity and shifted to higher frequencies with extended SO 2 exposure. The observed shift has been previously reported by several authors [30][31][32], ascribed to either pure frequency shift of a single band caused by the change in the strength of molecular interactions or the combined effect of two overlapping bands that differ in relative intensity. The shift in frequency is observed only after 90 min of sulfur poisoning.…”
Section: Influence Of Sulfur On Different Precious Metal Speciessupporting
confidence: 79%
See 2 more Smart Citations
“…These bands increased in intensity and shifted to higher frequencies with extended SO 2 exposure. The observed shift has been previously reported by several authors [30][31][32], ascribed to either pure frequency shift of a single band caused by the change in the strength of molecular interactions or the combined effect of two overlapping bands that differ in relative intensity. The shift in frequency is observed only after 90 min of sulfur poisoning.…”
Section: Influence Of Sulfur On Different Precious Metal Speciessupporting
confidence: 79%
“…In contrast, ceria-containing catalysts required higher temperatures for sulfur removal compared to other samples, probably caused by a large formation of very stable bulk sulfates during SO 2 poisoning procedure, as reported from DRIFTS measurements. Bounechada et al [32] indeed suggested that the high dynamic oxygen storage capacity (OSC) of ceria-containing materials leads to the diffusion of surface sulfates into the bulk, blocking some pores and inhibiting the access to active sites. Meanwhile, the remaining sulfur species on Ce-containing catalysts certainly affected the NO x stored stability by reducing the amount of NO x released after sulfation.…”
Section: Interpretation Of the Sulfur Poisoning And Regeneration Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details on the preparation and characterisation of the Pt/SiO 2 sample can be found elsewhere 16 and thus we give only a brief description here. Silica powder (Kromasil Silica KR-300-10, Akzo…”
Section: Experimental and Theoretical Methods Sample Preparation And mentioning
confidence: 99%
“…The samples are from here referred to as Pt/Al, Pt/AlCe and Pt/Ce, respectively. Transient activity tests were performed with monolith samples in a continuous gas-flow reactor, which has been described in detail elsewhere [21]. The monolith samples were prepared by coating 200 mg of the respective powder catalyst onto cordierite monolith substrates (L=15 mm, ?=12 mm) as described in reference [20].…”
Section: Methodsmentioning
confidence: 99%